Hubungan Penggunaan Media Pembelajaran dengan Motivasi Belajar Sejarah Siswa di SMA Negeri 1 Ranah Pesisir - Putri, Junita Eka; Afriani, Rini (Lembaga Yasin AlSys, 2025)
Instructional media is a key component in supporting the success of the teaching and learning process, as it can enhance students’ motivation and understanding of lesson content. This study aims to analyze the relationship between the use of instructional media and students’ motivation to learn history at SMA Negeri 1 Ranah Pesisir, Pesisir Selatan Regency, West Sumatra. A quantitative ex post facto approach was used, with data collected through questionnaires distributed to 68 Grade XII students. Data were analyzed using simple linear regression with the assistance of SPSS software. Descriptive analysis showed that most students expressed agreement (57.35%) or strong agreement (42.65%) regarding their motivation to learn history. Pearson correlation testing indicated a positive and significant relationship between the use of instructional media and students’ motivation to learn history, with a correlation coefficient of 0.670 and a significance level of 0.000 (< 0.05). These findings suggest that the more effectively instructional media is used, the higher students’ motivation to learn history. The study underscores the importance of utilizing and diversifying instructional media to increase student engagement, and encourages teachers to continuously innovate in media use to create more engaging and effective learning experiences.